INTEGRATING GERIATRICS INTO THE ACUTE HOSPITAL SETTING: NOW OR IN THE FUTURE? - Fastenmeier Heribert; Leuca Mirela (Annals of the University of Oradea: Economic Science, 2009)
The demographic ageing of the population and its impact on social systems, economies or labor markets have often been analyzed and discussed in Germany. The German health care system is expected to face great challenges due to the “double-ageing” of the p